A superstrate and FSS‐loaded high gain circularly polarized twist waveguide array. Issue 3 (23rd December 2022) - Chandra, Avinash; Kumar, Rajkishor; Mishra, Naveen; Patil, Hemprasad Y.
Abstract: In this article, a superstrate and arrow‐shaped frequency selective surfaces (FSSs) embedded twist aperture array has been presented. In this article, a single arrow‐shaped FSS is kept in the E‐plane and the superstrate is kept above the aperture to form a circularly polarized twist waveguide array. Optimization and analysis have been carried out by commercially available software Ansys HFSS 15.0. The presented waveguide array has an input reflection coefficient ranging from 8.6 to 9.62 GHz and an axial ratio ranging from 8.7 to 9.37 GHz. Additionally, the presented array provides higher gain as compared to the conventional open‐ended WR‐90 twist waveguide.